A classical case of non-bacterial thrombotic endocarditis from pancreatic adenocarcinoma presenting as multiple strokes, myocardial infarction and acute limb ischaemia - SIA CHING HUI (Oxford University Press (OUP), 2021)
10.1093/omcr/omw084